MENYUSUN LAPORAN KEUANGAN SEDERHANA DENGAN MICROSOFT EXCEL - Ririh Dian Pratiwi (MEDIA, 2012)
Accounting is an information system that measures business activities, processes the data into a statement, and communicate the results to decision-makers who will make decisions that could affect business activity. The information generated in an accounting system called financial statement. Through Microsoft Excel, the financial statement can be simply prepared with a shorter cycle, from preparation ofÂ journal to simple financial statement. When recording of each transaction for a certain period has been done, then the next step is preparing financial statement. The main financial statement for an individual firm is balance sheet, income statementÂ and statement of owners equity. This article only examines the preparation of income statement and balance sheet. Arranging the balance sheet and income statement by using a Microsoft Excel worksheet.